Dealing with impoverishment: sourcing and selling food in Masvingo - Muzvidziwa, Victor N. (University of Zimbabwe Publications, 2016)
Sourcing and selling food are the main concerns of this article. Food vending was not a strategy to climb out of poverty: it was at best a coping strategy. The food-vending market niche demonstrated the existence of interconnections between food vendors and the formal and informal markets. The state and municipal authorities' responses to food vendors reflected narrowly-conceived, male-dominated, official development policies that marginalised the strategies for the alleviation of poverty by women in the informal sector. The way officials treated food vendors demonstrated the existence of competing and conflicting rationalities between male decision-makers and poor women. Those in authority in Masvingo seemed to be propelled in their actions by the desire to control. On the other hand, my Masvingo respondents strove to resist and circumvent the system of controls put in place by the powerful. My respondents' concern was to engage in those activities that contributed to the livelihood of their households.